2019
DOI: 10.2166/ws.2019.131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diffusion and dispersion of contaminants in water distribution networks modelling and monitoring

Abstract: In recent years, there has been a need to seek adequate preventive measures to deal with contamination in water distribution networks that may be related to the accidental contamination and the deliberate injection of toxic agents. Therefore, it is very important to create a sensor system that detects contamination events in real time, maintains the reliability and efficiency of measurements, and limits the cost of the instrumentation. To this aim, two problems have to be faced: practical difficulties connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The analysis of solute dispersion under the action of both longitudinal diffusion and radial dispersion shows that when the flow velocity in the pipeline is low, the radial diffusion process has a great influence on the results. On the contrary, the radial diffusion process has little effect on the results (Aris 1956;Piazza et al 2020;Ozdemir et al 2021).…”
Section: Introductionmentioning
confidence: 94%
“…The analysis of solute dispersion under the action of both longitudinal diffusion and radial dispersion shows that when the flow velocity in the pipeline is low, the radial diffusion process has a great influence on the results. On the contrary, the radial diffusion process has little effect on the results (Aris 1956;Piazza et al 2020;Ozdemir et al 2021).…”
Section: Introductionmentioning
confidence: 94%
“…This is advantageous from a computational point of view as it does not produce particular significant errors in purely turbulent flow regimes. Nevertheless, diffusive-dispersive processes assume great importance when low velocities and laminar/transition flow regime take part and affect the positioning of the monitoring system, as highlighted in Piazza et al (2020) [2].…”
Section: Introductionmentioning
confidence: 99%
“…EPANET [1] is the most commonly used software for water distribution network simulations and uses an advective approach which cannot efficiently analyze contaminant dispersion in the networks. Piazza et al [2] conducted experiments where it was shown that dispersive and diffusive processes must be incorporated in the transport model for less turbulent fluid flows to achieve more accurate results than the pure advection model. Also, EPANET assumes complete mixing in all network junctions, which can be valid only in the case of a single outlet or if there is considerable distance between two junctions.…”
Section: Introductionmentioning
confidence: 99%